Yo-yo reflux in partial duplication of ureter: A diagnosis on the color and pulse Doppler study - Kamini Gupta; Ritu Galhotra; Kavita Saggar (Wolters Kluwer Medknow Publications, 2013)
The diagnosis of yo-yo reflux in patients with partial collecting system duplications is difficult. We report a case of recurrent urinary tract infections due to partial duplication of the collecting system in which yo-yo reflux is demonstrated with color and pulse wave Doppler. Our aim is to highlight the fact that radiologists and clinicians should be aware of this noninvasive, inexpensive, and easily accessible modality so as to diagnose this phenomenon more frequently in future.